Patch grafting, strategies for transplantation of organoids into solid organs such as liver. (October 2021) - Zhang, Wencheng; Lanzoni, Giacomo; Hani, Homayoun; Overi, Diletta; Cardinale, Vincenzo; Simpson, Sean; Pitman, Wendy; Allen, Amanda; Yi, Xianwen; Wang, Xicheng; Gerber, David; Prestwich, Glenn; et al.
Abstract: Epithelial cell therapies have been at an impasse because of inefficient methods of transplantation to solid organs. Patch grafting strategies were established enabling transplantation of ≥10 7th organoids/patch of porcine GFP+ biliary tree stem/progenitors into livers of wild type hosts. Grafts consisted of organoids embedded in soft ( 100 Pa) hyaluronan hydrogels, both prepared in serum-free Kubota's Medium; placed against target sites; covered with a silk backing impregnated with more rigid hyaluronan hydrogels ( 700 Pa); and use of the backing to tether grafts with sutures or glue to target sites. Hyaluronan coatings ( 200–300 Pa) onto the serosal surface of the graft served to minimize adhesions with neighboring organs. The organ's clearance of hyaluronans enabled restoration of tissue-specific paracrine and systemic signaling, resulting in return of normal hepatic histology, with donor parenchymal cells uniformly integrated amidst host cells and that had differentiated to mature hepatocytes and cholangiocytes. Grafts containing donor mature hepatocytes, partnered with endothelia, and in the same graft biomaterials as for stem/progenitor organoids, did not engraft. Engraftment occurred if porcine liver-derived mesenchymal stem cells (MSCs) were co-transplanted with donor mature cells. RNA-seq analyses revealed that engraftment correlated with expression of matrix-metalloproteinases (MMPs), especially secreted isoforms that were found expressed strongly by organoids, less so by MSCs, and minimally, if at all, by adult cells. Engraftment with patch grafting strategies occurred without evidence of emboli or ectopic cell distribution. It was successful with stem/progenitor organoids or with cells with a source(s) of secreted MMP isoforms and offers significant potential for enabling cell therapies for solid organs.